A colorimetric chemosensor for selective detection of copper ions. (17th September 2020) - Kim, Ahran; Chae, Ju Byeong; Rha, Chang Joo; Kim, Cheal
Abstract: A water‐applicable hexamethylbenzene (HMB) chemosensor, (E)‐2‐((2‐hydroxy‐3‐methoxybenzylidene)amino)benzamide, displayed a selective colour change from colourless to yellow in the existence of copper ions. The detection limit was computed as 1.57 μmol/L, which is substantially lower than the World Health Organisation guideline (31.5 μmol/L) for copper ions. Probe HMB could also sense and quantify copper ions in real water samples. The coordination mode of HMB to copper ions was demonstrated through Job plot, electrospray ionisation mass spectroscopy and proton nuclear magnetic resonance titration, and was also supported by theoretical studies.